2021
DOI: 10.3390/plants10040762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multispectral Pulsed Light-Emitting Diodes on the Growth, Photosynthetic and Antioxidant Response of Baby Leaf Lettuce (Lactuca sativa L.)

Abstract: The effect of multicolor pulsed light-emitting diode (LED) irradiation on lettuce “Defender” growth, photosynthetic performance and antioxidant properties was studied. The experiments were designed to compare the continuous and pulsed lighting (0.5, 1 kHz; 50% duty ratio) effects of B450, G520, R660 and FR735 lighting components, maintaining total diurnal integral light quantity (DLI 14.4 mol m−2 day−1) constant during the 16-h photoperiod. The results showed that lettuce grown under pulsed irradiation display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The carotenoids contents of lettuce were sharply enhanced by pulsed lighting due to pulsed light and had a remarkable effect on increasing photosynthetic rate in lettuce ( Miliauskienė et al, 2021 ). Thus, different frequencies of supplemental blue light could promote the early color change and maturation of tomato fruits; this could be attributed to blue light regulating the transcriptional levels of light transcription factors such as SlPIFs and SlHY5 gene and mature promoter gene SlRIN , thus affecting the process of fruit lycopene metabolism ( Xie et al, 2019 ; Dong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carotenoids contents of lettuce were sharply enhanced by pulsed lighting due to pulsed light and had a remarkable effect on increasing photosynthetic rate in lettuce ( Miliauskienė et al, 2021 ). Thus, different frequencies of supplemental blue light could promote the early color change and maturation of tomato fruits; this could be attributed to blue light regulating the transcriptional levels of light transcription factors such as SlPIFs and SlHY5 gene and mature promoter gene SlRIN , thus affecting the process of fruit lycopene metabolism ( Xie et al, 2019 ; Dong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CRY2 overexpression increased flavonoid and lycopene levels in ripe tomato fruits ( Giliberto et al, 2005 ). Compared to continuous lighting, pulsed light increased polyphenols contents and the antioxidant capacity of lettuce ( Miliauskienė et al, 2021 ) and wheat plants ( Dong et al, 2015 ), which could be due to the stimulating effect of pulsed light on gene expression and activity rates of the key enzymes related to phenylpropanoid biosynthesis. In this study, the phenolics and flavonoids content under supplementary blue light treatments were significantly higher than CK ( Figures 5B,C ) and higher levels of phenolics and flavonoids were observed in higher frequencies of supplemental blue light ( Figures 5B,C ).…”
Section: Discussionmentioning
confidence: 99%
“…These authors showed that leaves left in darkness after UV-B treatment had substantially higher chlorophyll content and photosynthetic efficiency than those kept in constant light. In another study it was also observed that irradiation of light-emitting diodes substantially increased chlorophyll a and b content, leaf area, and overall growth in lettuce (Miliauskienė et al, 2021). Lately, it was reported that the reduction in leaf expansion in UV-B-irradiated leaves was imputed to the decline in cell production and shortened growth zone (Fina et al, 2017).…”
Section: Leaf Area/sizementioning
confidence: 93%
“…And its economic effect is achieved not only due to the high energy efficiency of LED light sources, their high reliability (the lifetime is more than 10 times higher than that of HPS lamps) but also, due to fundamentally new capabilities of agricultural technology to increase cultivation productivity for by optimizing the growth and development of plants by controlling the spectral composition and radiation intensity of LEDs at all stages of ontogenesis. Thus, numerous studies have shown the effects of LEDs on plants, such as elongation, axillary shoot formation, leaf anatomy, and rhizogenesis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%